Design, Control and Applications of Mechatronic Systems in Engineering 2017
DOI: 10.5772/67459
|View full text |Cite
|
Sign up to set email alerts
|

Remote Laboratories for Teaching and Training in Engineering

Abstract: Typical mechatronic systems are a combination of advanced technologies involving several disciplines. This multidisciplinary approach to the development of industrial applications provides great opportunities for the implementation of e-learning environments and collaborative schemes. Engineering education, in particular, benefits from many of these advances, among which, virtual instrumentation is a useful tool for the development of virtual environments, e-learning spaces and, particularly, remote laboratori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A group from Mexico and the UK have created a series of remote mechatronics and electrical laboratories, which can be both be controlled and data acquired remotely, using LabVIEW software via a webserver. 8 The work reported on three laboratories: an electropneumatic system, control of AC motors and residential wiring circuits. A small study of student feedback reported that students like the interface and can follow the experiments while lectures are being conducted.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A group from Mexico and the UK have created a series of remote mechatronics and electrical laboratories, which can be both be controlled and data acquired remotely, using LabVIEW software via a webserver. 8 The work reported on three laboratories: an electropneumatic system, control of AC motors and residential wiring circuits. A small study of student feedback reported that students like the interface and can follow the experiments while lectures are being conducted.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A group from Mexico and the UK have created a series of remote mechatronics and electrical laboratories, which can be controlled with data acquired remotely, using LabVIEW software via a webserver 8 . The work reported on three laboratories: an electropneumatic system, control of AC motors and residential wiring circuits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The subject of the study was the technology of organizing practical work of students at home, as access to special equipment was significantly limited, and virtual laboratory work does not give a complete immersion in the subject area of practiceoriented courses. At the same time, it should be noted that there are a large number of works on the creation of technologies for remote control of research equipment [1][2][3], as well as on virtual twins of products, processes, and technologies [4][5][6]. In spite of this, all the mentioned technologies do not allow students to get practical skills by working with their own hands taking into account the peculiarities of real equipment operation, conducting experiments, etc.…”
Section: Introductionmentioning
confidence: 99%